2013
DOI: 10.1002/ccd.25002
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of surgical cutdown versus percutaneous access in transfemoral TAVR

Abstract: Objectives: To compare iliofemoral arterial complications with transfemoral transcatheter aortic valve replacement (TF-TAVR) utilizing surgical cutdown versus percutaneous access with closure devices in a randomized trial. Background: Major vascular complications following TAVR are a significant risk of the procedure. There are no randomized data comparing whether access method in TF-TAVR influences the risk of such complications. Methods: From June to December 2011, 30 consecutive patients undergoing TF-TAVR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
1
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 20 publications
7
37
1
1
Order By: Relevance
“…Our results are in line with previous studies that compared the two different vascular access techniques . Two retrospective analyses and one small randomized study in patients undergoing transfemoral TAVI showed acceptable immediate safety and feasibility for both strategies .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are in line with previous studies that compared the two different vascular access techniques . Two retrospective analyses and one small randomized study in patients undergoing transfemoral TAVI showed acceptable immediate safety and feasibility for both strategies .…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in patients undergoing non‐TAVI endovascular aortic aneurysm repair showed that these two strategies were clinically comparable . Moreover, recently, one small randomized study and two retrospective single‐center surveys indicated that surgical and percutaneous approaches were both acutely feasible and safe for patients undergoing TAVI . Nevertheless, there is still scarce information about the impact of each vascular access technique on the long‐term outcomes of high‐risk patients undergoing TAVI.…”
Section: Introductionmentioning
confidence: 99%
“…Although it confirmed the feasibility of the PC approach, this study was underpowered to evaluate the end point of vascular outcomes. 15 An additional recent analysis showed unadjusted decreased length of stay in PC patients when compared with that in OS patients, but adjusted analyses of vascular outcomes and length of stay were not performed. 16 The largest study to date is based on the Pooled-Rotterdam-Milano-Toulouse in Collaboration (PRAGMATIC) initiative at 5 European centers.…”
Section: Discussionmentioning
confidence: 99%
“…In all these phases vascular access complications such as plaque disruption, local dissection, aneurysm formation, stenosis/occlusion, and even acute thrombosis, with consequent acute limb ischemia, can occur [21,22] . Moreover, the lesser invasive percutaneous method in an experienced center is associated with similar rates of major and minor vascular complications [23] and with lower access site infection and bleeding, and shorter hospital stay compared to the surgical approach [24] . While the Edwards SAPIEN valve is implanted through a 22 or 24 F arterial sheath (about 8 and 9 mm external diameter), the CoreValve and the Edwards SA-PIEN XT valve are delivered through a 16-20 F sheath (about 7 mm external diameter).…”
Section: Hemostasis Techniques Used In Tavimentioning
confidence: 99%